2011
DOI: 10.1038/oby.2011.186
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Oxygen Consumption Change Predicts Left Ventricular Relaxation Improvement in Obese Humans After Weight Loss

Abstract: Obesity adversely affects myocardial metabolism, efficiency, and diastolic function. Our objective was to determine if weight loss can ameliorate obesity-related myocardial metabolism and efficiency derangements and that these improvements directly relate to improved diastolic function in humans. We studied 30 obese (body mass index [BMI]>30kg/m2) subjects with positron emission tomography (myocardial metabolism, blood flow) and echocardiography (structure, function) before and after marked weight loss from ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 35 publications
2
39
1
Order By: Relevance
“…In accordance with this view, a recent study by Lin et al (27) reported reduced oxygen consumption in hearts from obese patients subjected to dietary weight loss. The authors argued that the reduced oxygen consumption could independently predict improved LV relaxation (23), which in turn implies that myocardial oxygen consumption may be mechanistically important in determining cardiac relaxation.…”
Section: Discussionsupporting
confidence: 65%
“…In accordance with this view, a recent study by Lin et al (27) reported reduced oxygen consumption in hearts from obese patients subjected to dietary weight loss. The authors argued that the reduced oxygen consumption could independently predict improved LV relaxation (23), which in turn implies that myocardial oxygen consumption may be mechanistically important in determining cardiac relaxation.…”
Section: Discussionsupporting
confidence: 65%
“…In support of UCPs contributing to the metabolic derangements in diabetes, mitochondria isolated from diabetic mouse hearts have elevated rates of oxygen consumption, increased uncoupled respiration, and reduced efficiency (13). Similar phenotypes have been observed in the hearts of diabetic patients through the use of positron emission tomography (PET) metabolic imaging (59).…”
Section: Cardiac Mitochondria In Diabetesmentioning
confidence: 68%
“…Weight-loss interventions have not only been shown to decrease myocardial FFA uptake without changing insulinstimulated myocardial glucose uptake, 110 but also to reduce myocardial fatty acid oxidation (per gram of LV), and that this decreased fatty acid oxidation is linked to decreased myocardial oxygen consumption (myocardial oxygen uptake per gram of LV). 111 When put together, this strengthens the evidence that increased fatty acid uptake and oxidation in obesity is linked to decreased cardiac efficiency, and that weight loss partially reverses these effects. In addition to this, moderate dietary weight loss has been shown to significantly reduce myocardial triglyceride content 112 and improve both myocardial energetics and diastolic function in obese subjects without cardiovascular risk factors.…”
Section: The Effects Of Weight Loss On Myocardial Metabolismmentioning
confidence: 48%